Realities, Challenges and Benefits of Antimicrobial Stewardship in Dairy Practice in the United States - Pamela L. Ruegg (Microorganisms, 2022)
The use of antimicrobials for the treatment of food-producing animals is increasingly scrutinized and regulated based on concerns about maintaining the efficacy of antimicrobials used to treat important human diseases. Consumers are skeptical about the use of antibiotics in dairy cows, while dairy producers and veterinarians demonstrate ambivalence about maintaining animal welfare with reduced antimicrobial usage. Antimicrobial stewardship refers to proactive actions taken to preserve the efficacy of antimicrobials and emphasizes the prevention of bacterial diseases and use of evidence-based treatment protocols. The ability to broadly implement antimicrobial stewardship in the dairy industry is based on the recognition of appropriate antimicrobial usage as well as an understanding of the benefits of participating in such programs. The most common reason for the use of antimicrobials on dairy farms is the intramammary treatment of cows affected with clinical mastitis or at dry off. Based on national sales data, intramammary treatments comprise < 1% of overall antimicrobial use for food-producing animals, but a large proportion of that usage is a third-generation cephalosporin, which is classified as a highest-priority, critically important antimicrobial. Opportunities exist to improve the use of antimicrobials in dairy practice. While there are barriers to the increased adoption of antimicrobial stewardship principles, the structured nature of dairy practice and existing emphasis on disease prevention provides an opportunity to easily integrate principles of antimicrobial stewardship into daily veterinary practice. The purpose of this paper is to define elements of antimicrobial stewardship in dairy practice and discuss the challenges and potential benefits associated with these concepts.